Ultrastructural evaluation of bronchial lymphoid aggregates and lymphoid nodules in calves at different ages - Abu Bakar @ Zakaria, Md Zuki; Saw, Po Po; Saad, Mohd Zamri (Veterinary Association Malaysia, 2009)
This study was conducted with the aim of defining the ultrastructure of bronchial lymphoid aggregates and lymphoid nodules of the bronchus-associated lymphoid tissue (BALT) in 3-, 6- and 8-month-old calves. A total of 9 calves divided into 3 age groups of 3 calves in each group was used in this study. Samples of the lungs were taken systematically and processed for scanning electron microscopic (SEM) and transmission electron microscopic (TEM) examinations. The results revealed differences between the epithelium of lymphoid aggregates and lymphoid nodules. SEM showed the absence of cilia over the lymphoid nodules but not over aggregates. Flattened, non-ciliated epithelial cells which may be precursors of the M cells were found in lymphoepithelium (LPE) of 3-month-old calves over nodules. The non-ciliated epithelial cells over nodules in 6- and 8-month-old calves were columnar in bronchi, but in bronchioles they were cuboidal. However, in the 3-month-old calves, some were columnar and some flattened in bronchi and in bronchiole, they were cuboidal. Transmission electron microscopic examination showed the presence of two types of M cells found in the LPE. Type 2 M cells were found in 3- and 6-month-old calves while type I M cells predominated in the bronchi in 6- and 8-monthold calves. This work represents the first systematic investigation of the similarities and differences in the ultrastructure of lymphoid aggregates and lymphoid nodules in calves and changes therein as a function of age.